1999
DOI: 10.1046/j.1537-2995.1999.39111185.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of human T‐lymphotropic virus (HTLV) types I and II polymerase chain reaction and several serologic assays in screening a population with a high prevalence of HTLV‐II

Abstract: In this sample set from a population at high risk for HTLV-II, screening with HTLV-I/II PCR had lower sensitivity and specificity than that with EIAs. However, 4.1 to 10.8 percent of samples were PCR positive but seronegative for HTLV-I or -II, and their true infection status remains undetermined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
17
0
2
Order By: Relevance
“…where infection is not endemic, such as metropolitan France (0.0033 per thousand) (8) and the United States (0.035%) (22,24,32), but much lower than the rates reached in Cameroon (11% among a rural population) (28) and in Congo (3% among pregnant women) (42). This high frequency of indeterminate results clearly emphasizes the difficulty in assessing the real HTLV-1 seroprevalence, especially in tropical areas where indeterminate WB patterns peak and lead to misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where infection is not endemic, such as metropolitan France (0.0033 per thousand) (8) and the United States (0.035%) (22,24,32), but much lower than the rates reached in Cameroon (11% among a rural population) (28) and in Congo (3% among pregnant women) (42). This high frequency of indeterminate results clearly emphasizes the difficulty in assessing the real HTLV-1 seroprevalence, especially in tropical areas where indeterminate WB patterns peak and lead to misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…There are several diagnostic methods for the detection of HTLV-1 and -2 antibodies, including enzyme immunoassays (EIAs), the particle agglutination assay (PAA), immunofluorescence assays, Western blotting (WB), and the radioimmunoprecipitation assay (3,4,7,10,21,24,37,45; Stramer et al, Abstr. 52nd Annu.…”
mentioning
confidence: 99%
“…The results indicated that WB failed to detect infection by HTLV type 2, and this was also observed in two other cases that were not included in this study. Previous studies have shown that the confirmatory sensitivity of WB for HTLV-2 is worse than for HTLV-1 and presents a greater frequency of indeterminate or false negative results [28][29][30][31] . Two (5%) out of the 40 WB-positive samples from blood donors did not present reactivity in the WB test for either of the recombinant proteins (rgp46-I or rgp46-II).…”
Section: Discussion Ethics Committee Approval This Study Was Approvedmentioning
confidence: 97%
“…The development of new EIA kits for HTLV that use recombinant proteins and synthetic peptides has increased the sensitivity and specificity of such kits, in comparison with kits that use viral lysate [25][26][27] . In contrast, the WB test for HTLV-1/2 has shown little development over recent years, and is unsuitable for blood banks because of its high costs and high proportion of indeterminate results [28][29][30][31][32] . This situation suggests that there is a need to confirm virus infection by means of molecular tests.…”
Section: Discussion Ethics Committee Approval This Study Was Approvedmentioning
confidence: 99%
“…The serologic and PCR results in this animal were consistent with reports of rare HTLV-1-infected individuals who are serologically negative while PCR positive for the virus in their PBMCs. [40][41][42] Another rabbit of interest in the ACH.195 group was R20, which mounted an antibody response not only to HTLV-1 Gag and Env proteins, but also to the HTLV-2 SU protein. In this rabbit, the antibody response to HTLV-2 SU was stronger than that mounted against HTLV-1 SU.…”
mentioning
confidence: 99%